Artistic and aesthetic way of hand positioning in «Kui tartys» art (Eurasian Journal of Philology Science and Education, 2016)
The art of kui has taken its origin and adapted to the Kazakh people, swept for many centuries by a mature individual schools master artists transmitted through hearing from generation to generation. About development of dombra kyuis, the formation of the traditional performing schools, a stylistic and structural features kyuis wrote in writings, researchers, ethnographers A. Zhubanov, G. Bisenova, B. Amanov, A. Muhambetova, A. Seydimbek, S. Utegalieva, S. Raimbergenova, kyuevedy H. Tastanov, T. Mergaliev, K. Akhmediyarov, A. Toktagan, T. Asemkulov, B. Iskakov, A. Raimbergenov, K. Saharbaeva and others. In this article the author reviews style of playing of one of the ancient forms of the Kazakh dombra art «tartys», which has been preserved by an oral tradition, and the role of the right and left hands in the performance of this type of art (pick, vibration, fingering). In addition, the author touches upon such topics as the formation of graphic picks right hand in performing contemporary schools, continuation of the tradition «kui tartys» (through video extant in the archive records D. Nurpeisovoy, M. Uskenbaeva) and its promotion by the latest methods (concert performance in a variety of formats).
Keywords: kui tartys; dombyra’s art; kui artist; competition; pick; hand position; performing schools